School librarian - marketing specialist?! - Banek Zorica, Mihaela; Špiranec, Sonja; Lazić, Nikolaj (2007)
Although marketing was primarily oriented toward the business sector i.e. profit oriented, more and more non-profit organizations are coping with the problem of promoting their services. Some of these non-profit organizations are school libraries. Therefore, authors have researched the current situation in school libraries regarding their marketing services and skills. The main purpose was to established whether school librarians are aware of the importance of of marketing in school libraries and whether they are following any marketing strategies or applying any marketing skills to promote their libraries.
Projekt MZOS
ENG